Mesoporous Metallic Cells: Design of Uniformly Sized Mesoporous Pt-Ru Hollow Particles with Tunable Shell Thicknesses - Ataee-Esfahani, H.; Liu, Jian; Hu, M.; Miyamoto, N.; Tominaka, S.; Wu, K.; Yamauchi, Y. (Wiley, 2013)
A new class of hollow mesoporous Pt–Ru and Pt particles with uniform size, named ‘mesoporous metallic cells’, are synthesized through a dual-templating approach using colloidal silica particles and non-ionic surfactants. To realize the full potential of mesoporous metals as electrocatalysts, the shell thicknesses, compositions, and hollow cavity sizes are precisely controlled.